Effects of timing of nitrogen application on grain yield of maize - e Silva, Paulo Sérgio Lima; e Silva, Paulo Igor Barbosa (Pesquisa Agropecuaria Brasileira, 2002)
A two-year study was carried out at Mossoró county, Brazil, with sprinkler irrigation, in order to evaluate the effects of timing of application of 120 kg/ha of N (ammonium sulphate) on grain yield of maize. The randomized blocks design with five replications and the following treatments were utilized: whole application of preplanting (1-0-0), side dressed at 25 (0-1-0) or at 45 (0-0-1) days after planting and split applications (0-1/3-2/3, 1/3-0-2/3, 1/3-2/3-0, 0-1/2-1/2, 1/2-0-1/2, 1/2-1/2-0, 0-2/3-1/3, 2/3-0-1/3, 2/3-1/3-0 and 1/3-1/3-1/3). The effect of treatments was independent of the effects of the years. The highest grain yield (4,960 kg/ha) was obtained with 0-1/3-2/3 treatment, but the other treatments propitiated similar grain yields, except the 1-0-0, 1/3-2/3-0 and 2/3-1/3-0 treatments that showed the lowest grain yields.
Keywords: Zea mays; fertilizers